A staff development program for public librarians in the National Capital Region, Philippines - Berdin, Glen P. (1998)
The primary objective of public libraries is to provide service to people from all walks of life. This study investigated the status of public librarians in the National Capital Region with the following objectives: (1) to identify the status of public librarians in terms of goals, capabilities, performance, and position; (2) to analyze the similarities and differences of the respondents' goals, capabilities, performance, and the position they are currently occupying; and (3) to formulate a needs based staff development program for public librarians in response to perceived needs. The descriptive method of research was used, employing a structured questionnaire as primary instrument. The questionnaire was formulated to draw the desired information, supplemented by personal interviews of respondents, regardless if they have passed or not the licensure examination as provided for by R.A. 6966. A universal sample included librarians occupying the positions of Librarian I, II, III, IV, and V.